(3GdebGeI GdfNdjI hTQMgGs - (3Ydj Hf YHO Gddg Hf eMeO Hf eMeO GdLPGej GdeGdbj GdfHGgj, GHf GdMSf,J (B792 (3g` s ((3YHOGddg eMeO Hf CMeO Hjf efUhQ GdLRGQi s)
(3ChdgG (B:s
(3bdJ CNGWH ef CLQi ef GdSQGJ PcQ GdYQGb Chd GdTQM(B: (3CeG HYO MeOGddg GdYdi GdYXje aEfi cfJ bO CedjJ s
(3BNQgG (B:s
(3jYJeO ef jba YdjgG ef GdBf Edi jhe GdeYGO hGdQMeGJ hGdHQcGJ JeJ GdebGeI hjJdhgG GdTQM BNQ GdTQM (B: (3hjG ef CeQg EPG CQGO TjFkG jbhd dg cf ajchf GdfUGFM s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdebGeI aj MhGQ Hjf fNdg hcQeIs
(3hai GdTQM ddeDda faSg ahGFO COHjg hJGQjNjgs
(3GdfSNI ebGHdIs
(3HgG fXGe GdJYbjHI s
(3cGf GdeDda MjkG SfI (B792 (3g`s
(3bQf GdfSN (B:s
Keywords: (3GdCOHs